2002
DOI: 10.1080/02724980143000505
|View full text |Cite
|
Sign up to set email alerts
|

Task-induced fatigue states and simulated driving performance

Abstract: States of fatigue are implicated in driver impairment and motor vehicle accidents. This article reports two studies investigating two possible mechanisms for performance impairment: (1) loss of attentional resources; and (2) active regulation of matching effort to task demands. The first hypothesis predicts that fatigue effects will be accentuated by high task demands, but the second hypothesis predicts that fatigue effects will be strongest in "underload" conditions. In two studies, drivers performed a stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
122
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 204 publications
(137 citation statements)
references
References 33 publications
(46 reference statements)
12
122
1
2
Order By: Relevance
“…as a consequence of low effort investment) may result in an impairment of effort regulation [3]. This is confirmed by Matthews and Desmond [8] who found an effort reduction as a consequence of a reduced awareness of performance impairment with the increase of fatigue.…”
Section: Theoretical Backgroundsupporting
confidence: 72%
“…as a consequence of low effort investment) may result in an impairment of effort regulation [3]. This is confirmed by Matthews and Desmond [8] who found an effort reduction as a consequence of a reduced awareness of performance impairment with the increase of fatigue.…”
Section: Theoretical Backgroundsupporting
confidence: 72%
“…However, when the perceived workload of the task is high, participants must mobilize additional effort to maintain safety and performance, and this additional effort may focus attention on the task, and mitigate the effects of stress on performance. Previous driver simulator studies have found that stress (Matthews, 1996) and fatigue (Matthews & Desmond, 2002) inductions have more serious adverse effects on vehicle control and attention to hazards during straight sections of roadway, as opposed to curved sections of roadway. These findings support an effort regulation model of stress and performance; contrary to resource theory, stress and fatigue may be most damaging when workload is low.…”
Section: Theories Of Performancementioning
confidence: 99%
“…One such task, of military relevance, is vehicle driving. Our previous studies (e.g., Matthews & Desmond, 2002) have shown that the driver's ability to control the vehicle while also monitoring for target stimuli may be impaired following a period of prolonged high workload. The aim for this study was to investigate subjective predictors of performance deficit during simulated vehicle operation, as a precursor to a later study using the TCD.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Two forms of latent performance decrements were supposed to play a role in this study: compensatory costs and subsidiary task failures (Hockey, 1997). In previous driving studies, measures of lateral vehicle control (heading error, steering reversals) have been shown sensitive for drivers' strategic regulation of mental effort (Fairclough, 2001;Matthews & Desmond, 2002). However, lateral control measures were confounded by the effects of the lane keeping assistance systems in this study and could not be used as clear indicators for drivers' strategic regulation of mental effort.…”
Section: The Influence Of Motivational Processes On Drivers' Reliancementioning
confidence: 59%